CRM unplugged : - Bligh, Philip (Wiley, 2004)
Building and maintaining a customer-centered enterprise cost-effectively is a hot topic and key business issue. This book provides the definitive work on how to derive return from investment. It answers the question: What is the real benefit of customer ERP? By knowing this answer corporations can avoid being disappointed with their implementation